Health education for pregnant and puerperal women in the pandemic by COVID-19: experience report - Jéssyca Tallyne Dantas de Oliveira Silva; Lucilene Rafael Aguiar; Maria das Neves Figueiroa; Maria Solange de Oliveira (Universidade de Pernambuco, 2021)
Objective: To describe the experience of innovating in the production and dissemination of health education material to guide pregnant and postpartum women in nursing consultation during the pandemic by COVID-19. Method: Descriptive study, of experience report. An intervention plan was divided into three stages: planning of the theme and theoretical survey; production of educational materials; and dissemination of the materials to the target audience and the community. Results: Three videos were produced, titled "Puerperium," "Breastfeeding," and "Contraception," made available via a playlist on the YouTube channel. Conclusions: The production of the videos proved to be a great alternative for sharing information to pregnant and postpartum women in the community, presenting new perspectives regarding the use of educational technologies in the context of basic health units. The realization of the intervention project reaffirms the role of the public university as a service provider to the population.